Coaches' and players' perceptions of health promotion activities in sport clubs. (March 2018) - Van Hoye, Aurélie; Heuzé, Jean-Philippe; Meganck, Jeroen; Seghers, Jan; Sarrazin, Philippe
Objectives: To better understand the role sports club coaches can play in health promotion (HP), as well as factors supporting this task, this study compared coaches' and players' perception of coaches' HP activities and tested whether coaches' basic need satisfaction predicted coaches' HP activities mediated by self-determined motivation to coach. Design: A cross-sectional design was employed. Multivariate analyses were used to compare coaches' and players perceptions of HP, while structural equation modelling was used to test the model. Setting: Community football clubs in the south east of France. Method: A sample of 101 coaches and 404 players from 18 soccer clubs completed a questionnaire assessing HP activities' perceptions. Coaches also completed scales on basic need satisfaction and self-determined motivation. Results: Similar patterns were found for coaches and players' answers, with only a few differences, especially in the Respect for Oneself and Others dimension. Moreover, basic need satisfaction predicted Respect for Oneself and Others through self-determined motivation, while self-determined motivation was related to a Healthy Lifestyle, but basic need satisfaction and self-determined motivation were not linked to Substance Use . Conclusion: Results highlight few differences between coaches' and players' perceptions of coaches' HP activities. Coaches' HP activities are sparse, but seem to be perceived by their players. Self-determined coaches were more likely to promote a Healthy Lifestyle and Respect for Oneself and Others . The lack of relationship between motivational variables and Substance Use could potentially reflect the complexity of drug and alcohol prevention in sports clubs.